Issue Information. Issue 1 (18th June 2020) - Unknown
Abstract : Cover : In Wood (http://doi.org/10.1002/cpcy.73 ), the image shows AML MRD, monocytic. Progenitors and monocytes gated using CD45 versus SSC identify an abnormal population of immature monocytes (orange) that differs from normal CD34 + progenitors (red), monocytes (magenta), maturing neutrophils (green), and B cells (cyan) by having abnormal CD34 (absent) with CD117, HLA‐DR (variably decreased), CD33 (dimmer than monocytes, but brighter than neutrophils), CD15 (increased), CD13 (absent), CD64 (more variable than normal), CD14 (absent), and CD56 (increased). Note that the absence of CD14 and presence of bright CD64 is normal for immature monocytes, but HLA‐DR should also be uniformly and brightly positive on immature monocytes but instead shows an aberrant, dramatic decrease in expression. Normal monocytic maturation with CD14 and HLA‐DR is well demonstrated in this sample (bottom center).